Lived experience of healthcare providers amidst war and siege: a phenomenological study of Ayder Comprehensive Specialized Hospital of Tigray, Northern Ethiopia - Awol Yemane Legesse; Znabu Hadush; Hale Teka; Ephrem Berhe; Bisrat Tesfay Abera; Fasika Amdeselassie; Hiluf Ebuy Abraha; Daniel Gebre; Alessandra N Bazzano (BMC, 2024)
Abstract Background Most wars are fought in poor countries and result in significant proportions of disabilities and mortalities. The consequences of wars and political instability on health workers and access to healthcare remain under-studied. This study aimed to explore the lived experience of healthcare providers amidst war and siege, in a teaching hospital in northern Ethiopia. Methods The study was conducted between February 2022 to March 2022. A qualitative phenomenological study was conducted between February to March 2022 with 20 healthcare providers working in Ayder Comprehensive and Specialized Hospital (ACSH), Tigray, Ethiopia, during the Tigray War. The study employed in-depth interviews. Results The main themes identified included the consequences of the siege on health service delivery at ACSH, personal survival threats posed by the siege, immediate health consequences of the siege among care providers, and consequences of the siege on the motivation and energy of health professionals. Conclusions Health workers are exposed to a range of direct and indirect impacts of war, emphasizing the need to amend the conditions in which they live and work.